2015
DOI: 10.1128/jvi.03047-14
|View full text |Cite
|
Sign up to set email alerts
|

Thymic HIV-2 Infection Uncovers Posttranscriptional Control of Viral Replication in Human Thymocytes

Abstract: A unique HIV-host equilibrium exists in untreated HIV-2-infected individuals. This equilibrium is characterized by low to undetectable levels of viremia throughout the disease course, despite the establishment of disseminated HIV-2 reservoirs at levels comparable to those observed in untreated HIV-1 infection. Although the clinical spectrum is similar in the two infections, HIV-2 infection is associated with a much lower rate of CD4 T-cell decline and has a limited impact on the mortality of infected adults. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 49 publications
2
22
0
Order By: Relevance
“…The amount of virus in cell-free culture supernatants was quantified in terms mass of active reverse transcriptase (ng RT) using the Cavidi Lenti RT Activity kit (Cavidi Tech AB), a non-radioactive ELISA method that measures RT-dependent DNA synthesis in the extract normalized to a standard curve of recombinant HIV-1 RT protein. This test was shown to have similar efficacy for both viruses (Soares et al, 2011a;Nunes-Cabaço et al, 2015). Viral stocks were concentrated by ultracentrifugation (30 min/50,000 g/4°C; Beckmann L8-60M) before resuspension in culture medium supplemented with polybrene (3 lg/ml; Sigma) and used to infect unstimulated and TCRstimulated primary cells or stably transfected cell lines, at a dose of 0.853 ng RT/10 6 cells, during 3 h culture under standard conditions (37°C/5% CO 2 ).…”
Section: Virus Production and Hiv Infectionsmentioning
confidence: 92%
“…The amount of virus in cell-free culture supernatants was quantified in terms mass of active reverse transcriptase (ng RT) using the Cavidi Lenti RT Activity kit (Cavidi Tech AB), a non-radioactive ELISA method that measures RT-dependent DNA synthesis in the extract normalized to a standard curve of recombinant HIV-1 RT protein. This test was shown to have similar efficacy for both viruses (Soares et al, 2011a;Nunes-Cabaço et al, 2015). Viral stocks were concentrated by ultracentrifugation (30 min/50,000 g/4°C; Beckmann L8-60M) before resuspension in culture medium supplemented with polybrene (3 lg/ml; Sigma) and used to infect unstimulated and TCRstimulated primary cells or stably transfected cell lines, at a dose of 0.853 ng RT/10 6 cells, during 3 h culture under standard conditions (37°C/5% CO 2 ).…”
Section: Virus Production and Hiv Infectionsmentioning
confidence: 92%
“…We and others previously reported that thymic function is preserved in HIV-2-infected individuals with low viral load (25). It was also recently shown that HIV-2 infection in thymocytes is impaired (26,27), which may contribute to the maintenance of high CD4 + T cell counts in HIV-2-infected patients. In this study, we measured sjTREC levels in total PBMC to estimate thymic function in HIC2.…”
Section: Cd45ramentioning
confidence: 99%
“…Of note, cell-associated DNA levels were significantly higher in sigmoid than in peripheral blood mononuclear cells (PBMC) (P ¼ 0.04). We further confirmed HIV-2 mucosal replication via immunohistochemistry using a previously validated anti-HIV-2 Gag-specific antibody, 22 using one biopsy per patient. Cells positive for HIV-2 Gag protein were detected in both sigmoid and ileum biopsies irrespective of antiretroviral treatment (sigmoid: 2/6 untreated and 3/7 ART patients; ileum: 1/5 untreated and 3/7 ART patients, Figure 1b).…”
Section: Evidence Of Hiv-2 Replication In the Gut Mucosamentioning
confidence: 80%
“…Standard curves were generated from serial dilutions of a plasmid containing both amplicons. 22 Cell-associated HIV-2 DNA was quantified in 50 ng of total DNA purified from PBMCs or from digested gut biopsies. The first step of the PCR was carried out in a 50 ml reaction mix containing the ''outer'' primers, dNTPs, MgCl2, Taq DNA Polymerase (GoTaq Flexi, Promega, Madison, WI), buffer, and 5 ml of DNA or of serial dilutions of the plasmid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation